Menilik Niat Masyarakat berpartisipasi dalam Crowdfunding pada Masa Pandemi Covid 19: (Studi Implementasi konsep Planned Behaviour Theory) - Purnama Putra (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
The Corona Virus Disease (COVID19) which began to spread throughout the world from 2020 mid-2021 has become a pandemic graphically experiencing several large waves that consistently take lives and have a sharp multidimensional impact. Islam teaches to always give alms both in difficult and happy situations which until now have been embedded in people's lives to care for others to the best of their ability. The crowdfunding movement is an embodiment of social care. This study aims to analyze what factors influence people to participate in the crowdfunding movement for solidarity in the pandemic era using the Planned Behavior Theory concept approach. The sample used in this study was 250 people, but only 235 data could be processed further using multiple regression analysis. The result of data processing is that the variables of attitude, subjective norm and perceived control simultaneously have a significant positive effect on public participation in the crowdfunding movement. The hope for further research is to take steps to optimize these factors in increasing public participation in crowdfunding as a form of social awareness and deepening related to crowdfunding management itself.